Faham keselamatan dalam budaya Jawa - Saksono, Ign. Gatut, 1953-; Djoko Dwiyanto, 1953- (Yogyakarta : Ampera Utama, 2012)
On blessing and cursing in Javanese social life and customs and philosophy.
Includes bibliographical references (p. 209-212).
Keywords: Javanese (Indonesian people) -- Social life and customs; Philosophy, Javanese; Blessing and cursing -- Indonesia -- Java; Java (Indonesia) -- Social life and customs